Stress Level Of Pregnant Women During The Pandemic Covid-19 - Wibowo, Dodik Arso; Muchsin, Enur Nurhayati (Chakra Brahmanda Lentera Institute, 2023)
PlagueCorona Virus Disease 2019 (Covid-19) makes everyone stressed and anxious because the transmission is very fast. Pregnant women during the Covid 19 pandemic do not rule out the possibility of experiencing stress due to the fear that something will happen to their pregnancy. Pregnancy with high stress levels can certainly have a negative impact on the mother and fetus. Stress is the body's non-specific response to every load demand and general reaction patterns and adaptations. Proper handling of pregnant women by the family can reduce the level of stress experienced by pregnant women. The purpose of this study was to determine the Stress Level of Pregnant Women During the Covid-19 Pandemic in Kalianyar Village, Ngronggot District, Nganjuk Regency. Descriptive research design, population and sample of 25 respondents with a sampling technique